Pengaruh Politik Indonesia Terhadap Penegakan Hukum Dalam Pemilihan Umum (Studi Tentang Pemilu Legislatif) - Mohammad Rafi’ie (Fakultas Hukum Universitas Darul Ulum, 2015)
In the general election (Election) 2004 legislative political representation in the general election isnot much different from the general election in the Orde Baru (Orba), ethics and professionalism politicsstill is not healthy, so it is difficult to distinguish between the era retormasi and New Order era thatalways raises political configuration repressive, and law enforcement is always income barriers aretriggered by unhealthy political,